Exploring the use of cost-benefit analysis to compare pharmaceutical treatments for menorrhagia - Sanghera, Sabina; Frew, Emma; Gupta, Janesh Kumar; Kai, Joe; Roberts, Tracy Elizabeth (Adis, 2015)
Background: The extra-welfarist theoretical framework tends to focus on health-related quality of life, whilst the welfarist framework captures a wider notion of well-being. EQ-5D and SF-6D are commonly used to value outcomes in chronic conditions with episodic symptoms, such as heavy menstrual bleeding (clinically termed menorrhagia). Because of their narrow-health focus and the condition’s periodic nature these measures may be unsuitable. A viable alternative measure is willingness to pay (WTP) from the welfarist framework.